Evaluation of service users' experiences of participating in an exercise programme at the Western Australian State Forensic Mental Health Services - Wynaden, Dianne; Barr, L; Omari, Omar; Fulton, A. (Wiley-Blackwell Publishing Asia, 2012)
Approximately 210 patients are admitted each year to the Western Australian State Forensic Mental Health Service, and most present with psychotic illness, along with other physical and mental comorbidities. In 2010, a healthy lifestyle programme, which included a formal exercise programme coordinated by an exercise physiologist, was introduced at the service. A self-report questionnaire was developed to obtain feedback on the programme, and 56 patients completed the questionnaire during the 6-month evaluation period. As well as providing patients with access to regular physical activity, the programme also supports the recovery philosophy, where patients work in partnership with forensic mental health staff. Overall, patients reported that the programme assisted them to manage their psychiatric symptoms, as well as improving their level of fitness, confidence, and self-esteem. In addition, patients received education about the importance of regular exercise to their mental health, and the role exercise plays in preventing chronic illness and obesity. While the benefits of exercise on mental health outcomes for people with depression and anxiety are well established, this evaluation adds to the evidence that such programmes provide similar benefits to people who have a psychotic illness and are hospitalized in an acute secure setting.